Maturidade em governança corporativa: pesquisa aplicada às cooperativas de crédito singulares no Município de Guarulhos - Nogueira, Vinicius Camilo Galvão (2015)
The Credit unions are financial institutions members of the national financial system and regulated by the Central Bank of Brazil. In order to corroborate the National Cooperative segment, this study aimed to diagnose and analyze the Maturity Level in Corporate Governance in Credit Unions Singles in the City of Guarulhos regarding the use of four Principles of Corporate Governance, (i) transparency, (ii) Equity, (iii) Accountability, (iv) Corporate Responsibility. The study of a descriptive nature involved the main leaders of the universe of the four credit unions located in Guarulhos and also made use of secondary data in the public domain. Developed a questionnaire with sixty questions with binary answers divided into the four principles of Corporate Governance. Each principle has fifteen questions divided into five levels (1 - Started 2 - Expanded, 3 - Institutionalized, 4 - Enhanced, 5 - Full) representing the degree of implementation of Corporate Governance in Credit Unions. Each level contains three specific issues. The applicability of the developed questionnaires was performed using the Survey Monkey questionnaire manager. The results show that the surveyed credit unions have Maturity Levels in Corporate Governance satisfactory, above fifty (50%) and less than seventy (70%), that is, it exists in a growing segment and constant concern for the Good Corporate Governance Practices